Key Mechanisms and Potential Targets of the NLRP3 Inflammasome in Neurodegenerative Diseases - Guan, Yadi; Han, Fang (Frontiers in Integrative Neuroscience, 2020)
Neurodegenerative diseases are neuronal disorders characterized by the loss of a large number of neurons in the human brain. Innate immunity-mediated neuroinflammation actively contributes to the onset and progression of neurodegenerative diseases. Inflammasomes are involved in the progression of the innate immune response and are responsible for the maturation of caspase-1 and inflammatory cytokines during neuroinflammation. The nucleotide-binding oligomerization domain leucine-rich repeat and pyrin domain-containing protein 3 (NLRP3) inflammasome, which is one of the most intensively investigated inflammasomes, has been reported to play a key role in neurodegenerative diseases. Here, we reviewed the mechanisms, role, and latest developments regarding the NLRP3 inflammasome with respect to three neurodegenerative diseases: Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS). Patient and animal model studies have found that abnormal protein aggregation of Aβ, synuclein, or copper–zinc superoxide dismutase‐1 (SOD1), which are the main proteins expressed in the three diseases re-spectively, can activate microglial cells, induce increased interleukin-1β (IL-1β) release, and activate the NLRP3 pathway, leading to neurodegeneration. In contrast, a deficiency of the components of the NLRP3 pathway may inhibit Aβ, synuclein, or SOD1-induced microglial activation. These studies indicate a positive correlation between NLRP3 levels and abnormal protein aggregation. However, in the case of ALS, not only microglia, but also astrocytes express increased NLRP3 levels and contribute to activation of the NLRP3 pathway. In addition, in this review, we also focus on the therapeutic implications of targeting novel inhibitors of the NLRP3 inflammasome or of novel drugs that mediate the NLRP3 pathway, which could play a role via NLRP3 in the treatment of neurodegenerative diseases.